Obstructive sleep apnea syndrome in patients with chronic idiopathic urticaria. Issue 6 (7th September 2020) - Alatas, Emine Tugba; Unal, Yasemin; Demir Pektas, Suzan; Kutlu, Gulnihal
Abstract: Urticaria is a disease which progresses with itchy papules and plaques called urtica, obstructive sleep apnea syndrome (OSAS) is defined as daytime sleepiness and obstructive apnea and hypopnea attacks during sleep. In this study, we aimed to investigate the relationship between urticaria and OSAS. Thirty‐one patients with chronic idiopathic urticaria were included in the study. Body mass indexes (BMIs) were calculated and polysomnography findings were recorded. Epworth Sleepiness Scale and Pittsburgh Sleep Quality Index were used to evaluate daytime sleepiness. The prevalence and severity of urticaria were calculated using the urticaria activity score (UAS). Chronic Urticaria Quality of Life Questionnaire was applied to patients. OSAS was detected in 13 (41.9%) of 31 patients. Then, 11 of the 13 patients had mild, 1 had moderate, and 1 had severe OSAS in the patient group. OSAS was not detected in the control group. A positive correlation was found between apnea‐hypopnea index and BMI, the UAS scores in the patient group (respectively, r = .537, P = .002, r = .407, P = .023). In this study, we found that the frequency of OSAS in patients with urticaria was more than that in the normal population. Doctors treating urticaria should consider a comorbidity disease such as OSAS and regulate the treatment according to these two diseases.